2019
DOI: 10.1186/s40623-019-1114-7
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of low-latitude spread F observed over Puer, China, during 2015–2016

Abstract: Statistical analysis of spread F (SF), recorded at Puer (PUR, 22.7° N, 101.05° E, Dip Latitude 12.9° N) during 2015-2016, was carried out to reveal its characteristics at the northern equatorial ionization anomaly. In our study, SF was categorized into four types, frequency spread F (FSF), range spread F (RSF), mix spread F (MSF) and strong range spread F (SSF). The statistical results presented that FSF and MSF were dominant over Puer. Most types of SF appeared mostly in summer months, except the maximum occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Strong seasonal/longitudinal variability of the EFIs occurrence rate has been recognized as a result of varying longitudinal gradient in the integrated E region conductivity, with a tendency of higher EFIs occurrence when the sunset terminator is aligned with the geomagnetic field lines (Carter et al, 2013;Dymond, 2012;Tsunoda, 1985). Other researchers found the positive correlation between the EFIs generation and solar activity, with EFIs detected more during solar maximum period and less during solar minimum years (Basu et al, 1988;Bhaneja et al, 2018;Carter et al, 2013;Lan et al, 2019;Pezzopane et al, 2013;Pietrella et al, 2017;Yu et al, 2018). It is well known that EFIs can affect the transionospheric radio wave, leading to so-called ionospheric scintillation, that is, rapid fluctuation in the amplitude and/or phase of the received signals (Alfonsi et al, 2013;Yeh & Liu, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Strong seasonal/longitudinal variability of the EFIs occurrence rate has been recognized as a result of varying longitudinal gradient in the integrated E region conductivity, with a tendency of higher EFIs occurrence when the sunset terminator is aligned with the geomagnetic field lines (Carter et al, 2013;Dymond, 2012;Tsunoda, 1985). Other researchers found the positive correlation between the EFIs generation and solar activity, with EFIs detected more during solar maximum period and less during solar minimum years (Basu et al, 1988;Bhaneja et al, 2018;Carter et al, 2013;Lan et al, 2019;Pezzopane et al, 2013;Pietrella et al, 2017;Yu et al, 2018). It is well known that EFIs can affect the transionospheric radio wave, leading to so-called ionospheric scintillation, that is, rapid fluctuation in the amplitude and/or phase of the received signals (Alfonsi et al, 2013;Yeh & Liu, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are partially consistent with those of Whalen (2002), who used an array of ionospheric sounders in the western American sector during solar maximum and showed that spread-F decrease with increasing Kp during equinox and summer, but they found no correlation in winter. Lan et al (2019) analysed ionograms recorded at the northern equatorial ionization anomaly in China. They reported a positive correlation for all types of spread-F in winter, an inverse correlation for SSF during equinox and summer, and for FSF in summer.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that at Huancayo, Peru, spread-F was more frequent on disturbed than on quiet days during the June solstice (local winter). Lan et al (2019) analysed ionograms recorded at the northern equatorial ionization anomaly in China. They reported a positive correlation for all types of spread-F in winter, and for RSF in all seasons, whereas the found an inverse correlation for FSF in summer.…”
Section: Plasma Bubbles Occurrence Ratementioning
confidence: 99%
“…They concluded that exist a connection between RSF occurrence and medium-scale TIDs due to gravity wave propagation. Lan et al (2019) suggested that night-time MSTIDs might play a signi cant role in the occurrence of RSF and FSF over Puer, China, at the northern EIA. Moreover, Pimenta et al (2008) showed that, in the Brazilian region, night-time spread-F can be caused by night-time mid-latitudes MSTIDs that propagate toward low latitudes.…”
Section: Comparison Between the Occurrence Characteristics Of Plasma ...mentioning
confidence: 99%